Inter-pad dead regions of irradiated FBK Low Gain Avalanche detectors. (1st October 2022) - Darby, B.; Mazza, S.M.; McKinney-Martinez, F.; Padilla, R.; Sadrozinski, H.F.-W.; Seiden, A.; Schumm, B.; Wilder, M.; Zhao, Y.; Arcidiacono, R.; Cartiglia, N.; Ferrero, M.; et al.
Abstract: Low Gain Avalanche Detectors (LGADs) are a type of thin silicon detector with a highly doped gain layer. LGADs manufactured by Fondazione Bruno Kessler (FBK) were tested before and after irradiation with neutrons. In this study, the inter-pad dead regions (IPDRs), defined as the width of the distances between pads, were measured with a TCT laser system. The response of the laser was tuned using β-particles from a 90 Sr source. These insensitive "dead zones" are created by a protection structure to avoid breakdown, the Junction Termination Extension (JTE), which separates the pads. The effect of neutron radiation damage at 1.5 × 10 15  neq /cm 2, and 2.5 × 10 15  neq /cm 2 on IPDRs was studied. These distances are compared to the nominal distances given from the vendor, it was found that at the high fluence there is a better matching of the insensitive region to the designed inter-pad region.